Pengaruh Likuiditas dan Aktivitas Terhadap Profitabilitas: Moderasi Ukuran Perusahaan pada Industri Produk Agrikultur - Cornelius Johanes Capestrano Dhityra; Liana Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to determine the effect of liquidity and activity on profitability and the role of firm size as a moderating variable in agricultural product industry companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study used quantitative research with panel data regression analysis and Moderated Regression Analysis (MRA). This study used a sample of 19 companies with a total of 76 observations selected through purposive sampling. Liquidity was measured using the Current Ratio (CR), activity using Total Asset Turnover (TATO), profitability using Return on Assets (ROA), and firm size using the natural logarithm of total assets. Data were processed using EViews version 12. The tests used were the classical assumption test, consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation; the panel data model selection test, consisting of the Chow Test, Hausman Test, and Lagrange Multiplier Test; and hypothesis testing, consisting of the F-test, t-test, and the coefficient of determination. The test results show that liquidity does not have a significant effect on profitability, while activity has a significant positive effect on profitability. Firm size is unable to moderate the effect of liquidity on profitability but can strengthen the effect of activity on profitability.